PENGUATAN PENDIDIKAN KARAKTER RELIGIUS MELALUI PENANAMAN NILAI AGAMA DAN MORAL DALAM MEMBENTUK AKHLAK DI KB ANGGREK RANDUPITU GEMPOL PASURUAN - Nanang Rokhman Saleh; Muhammad Syaikhon (DEVELOPMENT: Journal of Community Engagement, 2026)
So far, the implementation of religious character education through the instillation of religious and moral values in the Anggrek Randupitu Gempol Pasuruan Playgroup (KB) has been carried out quite well. The character education methods used include role modelling, habituation and singing. However, among the indicators of religious and moral values that have been prioritized by KB Anggrek for students, namely saying and responding to greetings, sharing and thanking each other, it turns out that they are still at the underdeveloped stage (BB). Therefore, the author is interested in carrying out community service activities at KB Anggrek Randupitu Gempol Pasuruan. This activity aims to increase knowledge and understanding about strengthening religious character education through instilling religious and moral values in forming morals. The method used was to gather the teachers of KB Anggrek, then provide counseling on strengthening religious character education through instilling religious and moral values in forming morals.  Extension using lecture, question and answer and evaluation methods. The level of knowledge of respondents can be determined by conducting a pre-test before the activity and a post-test after the activity.